Analysis of Performance of Disinvested Public Sector Enterprises Using DEA Approach - Naresh, G.; Thiyagarajan, S.; Mahalakshmi, S. (Indian Journal of Finance, 2011)
Disinvestment of Public Sector Enterprises was considered as an urgent necessity for the Indian economy for the last two decades. The primary goals of disinvestment of Central Public Sector enterprises include raising revenue for the state, promoting economic efficiency, reducing government interference, promoting wider share ownership, providing the opportunity to introduce competition, and to subject the Public Sector Enterprises to market discipline (Megginson and Netter, 2001). Due to the popularity of such activities, disinvestment studies are necessary to provide governmental institutions and investors with the background and knowledge to make appropriate decisions (Comstock, Kish, Vasconcellos 2003). Unlike the traditional methods of measuring financial performance, this paper examines the performance of disinvested public sector enterprises using the Data Envelopment Analysis (DEA) approach.